Serious games, interaction, and simulation : 5th International Conference, SGAMES 2015, Novedrate, Italy, September 16-18, 2015, Revised selected papers /: 5th International Conference, SGAMES 2015, Novedrate, Italy, September 16-18, 2015, Revised selected papers. (2016) - Unknown
No abstract available